2020
DOI: 10.3390/app10144981
|View full text |Cite
|
Sign up to set email alerts
|

Security Requirements Engineering Framework with BPMN 2.0.2 Extension Model for Development of Information Systems

Abstract: With recent advancements of technologies such as Internet of Things and cloud computing, security of information systems has emerged as a critical issue. This has created a need for elicitation and analysis of the security requirements at an early stage of system development. These requirements should also be expressed using visual notations that can encapsulate the vision of different stakeholders related to security. While business process management notation (version 2.0.2) is a widely used graphical repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Essentially, we found that (a) most of the current approaches require meta-model extensions that add a considerable number of security-related BPMN components, of which many are (b) excessively verbose, and thus difficult to manage (e. g., [21], [27], [32]) or fail to express security concepts in a format that is fully comprehensible to business experts, others propose only a theoretical or descriptive extension (e. g., [16], [18]). Threat modeling A threat profile security framework was proposed as a BPMN extension by Zareen et al in [32]. The authors leveraged the extension mechanism provided in BPMN 2.0 to model threat-based security requirements and introduced several graphical components for BPMN diagrams.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Essentially, we found that (a) most of the current approaches require meta-model extensions that add a considerable number of security-related BPMN components, of which many are (b) excessively verbose, and thus difficult to manage (e. g., [21], [27], [32]) or fail to express security concepts in a format that is fully comprehensible to business experts, others propose only a theoretical or descriptive extension (e. g., [16], [18]). Threat modeling A threat profile security framework was proposed as a BPMN extension by Zareen et al in [32]. The authors leveraged the extension mechanism provided in BPMN 2.0 to model threat-based security requirements and introduced several graphical components for BPMN diagrams.…”
Section: Related Workmentioning
confidence: 99%
“…Different ways to enrich the standardized BPMN with new concepts that reflect various security aspects already exist (e. g., [15], [18], [21], [27], [32]). However, if organizations have a large set of productive processes, adding supplementary information is often an unfeasible effort.…”
Section: Introductionmentioning
confidence: 99%
“…Semantics, namely the meaning of the requirements, allows the enhancement of accuracy and completeness, leading to a better understanding of hidden connections [8,10,[25][26][27]. In the literature, however, there are even domain-specific approaches, such as in [28], that deal with a specific case, and such as with security requirements that propose visual notations in order to express requirements. In [28], the authors propose the use of business process management notation (BPMN), a graphical representation for business requirements to define business processes.…”
Section: Related Workmentioning
confidence: 99%
“…Since security is the main concern of any organization, the level of security features available with the access management scheme should be well organized and arranged according to the time requirements. Previous authors [3][4][5][6] are mainly concerned with the analysis of information security components and risk analysis. This research focuses on managing privileged access using Active Directory services to provide an authentic and improved way of identity management for any organization.…”
Section: Introductionmentioning
confidence: 99%